PENYULUHAN HUKUM PERAN KOMUNITAS AKADEMIK DALAM PENDIDIKAN DI ERA DIGITAL DI SMA NEGERI 11 JAKARTA TIMUR - Edi Saputra Hasibuan; Widya Romasindah Aidy (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Indonesia highly respects traditional and culturalnorms that have existed for a long time, one of which is mutualcooperation. Gotong royong is the hallmark of Indonesia and thecapital of the Indonesian people to achieve independence and aaccurate reflection of communal values which are the breath ofIndonesian society. The value of communality is seen in variouscultures and local wisdom spread throughout the archipelago,like rewang culture, PKK collections and Siskamling habits.However, the use of digital media and COVID-19 pandemic hasshifted public gatherings from physical space to virtual or digitalspace. This pattern of interaction causes a large sense ofindividuality and is prone to conflict and division. Therefore,awareness is needed to build a stable academic community andpay attention to the spirit of togetherness and mutual cooperationto rebuild the cultural values of this communality.SMA Negeri 11 East Jakarta as the partner faced with theproblem of their lack of understanding regarding the role of theacademic community, especially for high school students in thedigital world.